2001
DOI: 10.1177/107906320101300206
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recidivism in Australian Juvenile Sex Offenders: Implications for Treatment

Abstract: Juvenile sex offenders charged with their first sexual offense were compared with recidivist juvenile sex offenders who had been charged with more than one sexual offense on a number of factors related to sexual offending. Participants were 70 male juvenile sex offenders, aged 13-21 years who were awaiting court disposition. Negative family history, negative family characteristics, school and learning problems, social skill deficits, deviant sexual experiences, deviant sexual fantasies, and cognitive distortio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 43 publications
2
52
0
2
Order By: Relevance
“…In the structural equation model developed by Kenny et al (2001), poor social skills was an exogenous variable that yielded direct paths to recidivism (standardized regression weight of .30) as well as to cognitive distortions (standardized regression weight of .29). There is some support in the empirical literature for two different facets of a "clinical risk" domain, a cognitive component that includes attitudes supportive of antisocial or deviant behavior (e.g., Gerdes, Gourley, & Cash, 1995;Spaccarelli et al, 1997) and a social/affective component that includes quality of interpersonal attachments, capacity for empathy and remorse, and emotional regulation (e.g., Marshall, Hudson, & Hodkinson, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In the structural equation model developed by Kenny et al (2001), poor social skills was an exogenous variable that yielded direct paths to recidivism (standardized regression weight of .30) as well as to cognitive distortions (standardized regression weight of .29). There is some support in the empirical literature for two different facets of a "clinical risk" domain, a cognitive component that includes attitudes supportive of antisocial or deviant behavior (e.g., Gerdes, Gourley, & Cash, 1995;Spaccarelli et al, 1997) and a social/affective component that includes quality of interpersonal attachments, capacity for empathy and remorse, and emotional regulation (e.g., Marshall, Hudson, & Hodkinson, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…with JSOs, in which such a distinction is rarely made (McCann & Lussier, 2008). Considering the case of the HRSD, it is unclear whether risk factors that are associated with sexual reoffending in youth (e.g., Hendriks, 2006;Kenny, Keogh, & Seidler, 2001;Prentky, Harris, Frizzell, & Righthand, 2000;Worling & Långström, 2006) are the same factors that contribute to the persistence of sexual offending into adulthood. In that regard, Knight, Ronis, and Zakireh (2009) recently demonstrated that JSOs who persist in adulthood were more likely than nonpersisting juvenile offenders to show evidence of sexual preoccupation and compulsivity, poor perspective taking, (adult/child) pornography use, hostility toward women, and superficial charm and grandiosity.…”
Section: Discussionmentioning
confidence: 99%
“…Other conclusions are limited; studies examining sexual fantasies of coercing adults have predominantly/completely sampled men who sexually offended against children [15,25] or investigated broader 'deviant' or 'crime' fantasy categories [16,26,27].…”
Section: Introductionmentioning
confidence: 99%